Investigation of microbial metal-sulfide interfacial environments under mineral bioleach simulated conditions - Africa, Cindy-Jade (Centre for Bioprocess Engineering Research, 2017)
This research pertains to bioleaching of copper containing ores with particular reference to the copper sulfide mineral chalcopyrite (CuFeS2). While it is focused on heap bioleaching, it has applications to stirred tank bioleaching operations. In the context of bioleaching, microbial extra-cellular polymeric substance (EPS) components are thought to complex chemical oxidants and extend the chemical reaction space available for mineral dissolution reactions, making the microbial-mineral-EPS interface the dominant active zone in terms of microbial oxidation and mineral dissolution. There is a limited understanding of microbial biofilm formation within a bioleach heap. The implication of various microorganisms having a set of defined or optimal conditions under which they colonise and proliferate is quite substantial. Understanding what creates favourable interfacial microenvironments enabling a sessile population to flourish (and thereby decrease lag time) has great implications for minimising costs and maximising productivity. Furthermore, limited work has been conducted on thermophilic microorganisms relevant to bioleaching. These microorganisms are pertinent to successful bioleaching at high temperatures, with work incorporating low grade ores and gangue mineralogy also being scarce. The aim of this research is to provide a thorough investigation into microbial-metal sulfide interfacial environments in situ, using a thermophilic archaeon M. hakonensis, low-grade metal-sulfide ores, a series of temperature regimes, heap-simulating conditions and an in depth extraction and analysis of the EPS produced under varied culturing conditions.